Resistência à corrosão em solução de hank de ligas e compósitos de magnésio submetidos à deformação plástica severa por torção sob alta pressão - Débora Ribeiro Lopes (2021)
To enable the use of magnesium in bioabsorbable implants, it is necessary to reduce the corrosion rate of this material. To improve these characteristics, studies are carried out on two work fronts, the development of new magnesium composites and the use of different processing techniques, such as the processing by severe plastic deformation, SPD (Severe Plastic Deformation). The objective of this work is to study the effect of High Pressure Torsion (HPT) on the corrosion resistance of pure magnesium, of some commercial Mg alloys and magnesium-based composites in HBSS (Hank's Balanced Salt Solution) synthetic body fluid. For this, samples of commercially pure magnesium, AZ31, AZ91, ZK60 alloys and composite of Mg with hydroxyapatite (MgHA) were processed by HPT. Corrosion resistance was studied by using electrochemical tests of anodic potentiodynamic polarization, EIS (Electrochemical Impedance Spectroscopy) and hydrogen evolution tests. The characterization of the oxides formed on the surface of the samples and the study of the morphological aspects of the corrosive process were carried out by SEM (Scanning Electron Microscopy) in conjunction with EDS (Energy Dispersive Xray Spectroscopy). To evaluate cytotoxicity, the MTT test (3- (4,5-dimethylthiazol2yl) -2,5 diphenyl tetrazoline bromide) was used. In Hank's solution, Mg and MgAl-Zn alloys showed passive behavior. HPT processing reduced the Mg passivation current density. Electrochemical impedance tests on the open circuit potential indicated greater resistance to corrosion of the AZ91 alloy. HPT processing increased the corrosion resistance of Mg and AZ31 alloy. The MgHA HPT composite showed greater corrosion potential in HBSS solution than Mg HPT, however, it had a generalized corrosion with a higher corrosion current. The results of electrochemical impedance spectroscopy indicated higher impedance for Mg processed by HPT in relation to the MgHA HPT composite, soon after the OCP stabilization, and different mechanisms. The composite showed an inductive behavior at low frequencies indicating adsorption of species on its surface or pitting corrosion. The hydrogen evolution tests indicated a delay in the peak of mass loss for the MgHA HPT composite, which is beneficial for the use of the composite as an implant, although the composite has presented a greater loss of mass in relation to magnesium. The presence of hydroxyapatite on the surface of the composite was 8 observed after immersion in HBSS solution with increased sample roughness after 60 h of immersion. The hydroxyapatite deposit showed cracks and detachment with time of immersion. The high cell viability demonstrated in the biological behavior assessment test indicates that the corrosion of the sample by the culture medium did not result in cytotoxic products. The use of HPT in samples of Mg and its alloys and to consolidate composites is of great importance in the study and development of new bioactive materials. The evaluation of the corrosion resistance of these materials in invitro tests in HBSS environment showed that under certain conditions the processing can increase the corrosion resistance and modify the corrosion mechanism.